Удосконалення вакуумних контакторів з моностабільними поляризованими електромагнітами - Лелюк, Микола Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.09.01 « Електричні машини й апарати» (14 – Електрична інженерія) – Національний технічний університет "Харківський політехнічний інститут", м. Харків, 2019 р. Дисертаційна робота присвячена удосконаленню вакуумних контакторів середніх напруг з моностабільними поляризованими електромагнітами зокрема щодо зменшення брязкоту головних контактів, що є однією з головних вимог для цих апаратів. Для досягнення цієї мети були поставлені задачі: – провести аналіз існуючих моделей (типів і конструкцій) вакуумних контакторів; – удосконалити математичну модель зварювання контактів під час виконання операції увімкнення вакуумного контактора; – обґрунтувати технічні рішення щодо розробки нових конструкцій бістабільних приводів, що використовують висококоерцитивні постійні магніти; – удосконалити математичну модель процесу увімкнення контактора; – розробити нові способи керування моностабільним поляризованим електромагнітом, з можливістю заміни високовартісних силових транзисторів та драйверів до них, гібридними системами; – розглянути можливість зменшення часових інтервалів між операціями увімкнення та вимкнення контактора. Об’єкт дослідження – нестаціонарні теплофізичні, електромеханічні та електромагнітні процеси в вакуумних контакторах для мереж середніх напруг. Предмет дослідження – бістабільні приводи на базі моностабільних поляризованих електромагнітів з поворотними пружинами та мікропроцесорні системи керування ними. Методи дослідження. Математичне моделювання електромагнітних, механічних та теплофізичних процесів у моностабільному поляризованому електромагніті для визначення раціональних лінійних розмірів частин магнітопроводу. Чисельне розв’язання звичайних та диференціальних рівнянь в часткових похідних проводиться в чисельних пакетах програм та програмах написаних і перевірених здобувачем, які враховують найбільш істотні взаємозв’язки між явищами. В роботі отримані такі наукові результати. У дисертаційній роботі вирішено науково-практичну задачу з удосконалення вакуумних контакторів середніх напруг з моностабільними поляризованими електромагнітами, зокрема щодо зменшення брязкоту головних контактів, що є однією з головних вимог для цих апаратів. Проведено аналіз вакуумних контакторів середніх напруг. Виявлено ряд недоліків, що стосуються як електромагнітів, так і систем керування ними. Запропоновано і реалізовано концепцію контакторів з бістабільними приводами на базі моностабільних поляризованих електромагнітів з поворотними пружинами, що використовують висококоерцитивні постійні магніти. Встановлено співвідношення між характеристиками моностабільного поляризованого електромагніта та характеристиками поворотної та контактних пружин, при яких забезпечуються вимоги до вакуумних переривників щодо швидкості руху та кількості відскоків контактів. Удосконалено математичну модель зварювання контактів при їх брязкоті. Визначено максимальне значення величини можливої сили зварювання контактів під час виконання операції увімкнення контактора. Удосконалено математичну модель процесу увімкнення контактора та проведено розрахунки динамічних характеристик електромагніта. На основі проведених розрахунків обрано раціональні параметри котушки електромагніта та ємності електролітичного конденсатора при яких буде забезпечено надійне спрацьовування контактора та виконані вимоги виробників вакуумних переривників відносно тривалості брязкоту контактів та швидкості їх замикання. Проведено експериментальні дослідження кількості та тривалості відскоків головних контактів вакуумного контактора при виконанні операції увімкнення. Встановлено, що новий контактор повністю відповідає вимогам виробників вакуумних переривників відносно тривалості та кількості відскоків, швидкості руху контактів при виконанні операцій увімкнення та вимкнення. Запропоновано і реалізовано концепцію мікропроцесорної гібридної системи керування моностабільними поляризованими електромагнітами на основі використання інтерфейсного реле з двома перемикаючими контактними групами та одного силового транзистора. Розроблено алгоритм роботи мікропроцесорної гібридної системи керування моностабільним поляризованим електромагнітом та методику експериментального визначення часових інтервалів між моментами комутації транзистора, керуючого обмоткою реле, і силового транзистора. Встановлено мінімальний інтервал між моментами комутації інтерфейсного реле та IGBT транзистора, яке дозволяє забезпечити координацію їх роботи. Розроблено дослідний зразок нового універсального вакуумного контактора з мікропроцесорною системою керування та гібридною комутацією кола живлення обмотки моностабільного поляризованого електромагніта. Керування контактором може відбуватися в двох режимах роботи, виконуючи функції як звичайного моностабільного контактора, так і контактора з механічною защіпкою, що робить його універсальним. Розроблені імітатори полюсів з вакуумними переривниками, які повністю відтворюють характеристики реальних переривників, імітуючи завдяки встановленим на них пружинах вплив на механічні характеристики вакууму та сильфонів, дозволяють проводити випробування на механічну зносостійкість без високовартісних вакуумних переривників. Встановлено, що робота мікропроцесорної гібридної системи керування по датчику положення зменшується загальний час увімкнення та вимкнення контактора. Матеріали дисертаційної роботи використовуються в навчальному процесі на кафедрі електричних апаратів НТУ "ХПІ" в дисциплінах спеціальності "141 – електроенергетика, електротехніка та електромеханіка" (спеціалізація "141.07 Електричні апарати"), курсовому та дипломному проектуванні та науково-дослідних роботах. Дисертаційна робота виконана на кафедрі електричних апаратів в рамках ініціативної науково-дослідної роботи Національного технічного університету "Харківський політехнічний інститут" К3301 "Удосконалення вакуумних комутаційних апаратів" (ДР №0119U002552), де здобувач був виконавцем окремих розділів. Договір з ТОВ "АВМ Ампер", м. Кременчук, про науково-технічне співробітництво та наукове консультування за темою "Удосконалення вакуумних комутаційних апаратів" (№ 33/227-2019), де здобувач був виконавцем окремих розділів.

Dissertation for the degree of Candidate of Technical Sciences in specialty 05.09.01 "Electric Machines and Apparatus" (14 – Electrical Engineering) – National Technical University "Kharkiv Polytechnic Institute", Kharkiv, 2019. The dissertation is devoted to the improvement of medium voltage vacuum contactors with monostable polarized electromagnets, in particular, to reduce the bounce of main contacts, which is one of the main requirements for these apparatus. To achieve this goal, the following tasks are set: – to carry out an analysis of existing models (types and designs) of vacuum contactors; – to improve the mathematical model of contact welding during the operation of switching on the vacuum contactor; – to substantiate the technical solutions for the development of new designs of bistable actuators using high-coercive permanent magnets; – to improve the mathematical model of the process of switching on the contactor; – to develop new ways to control a monostable polarized electromagnet, with the ability to replace expensive power transistors and drivers to them, by hybrid systems; – to consider the possibility of reducing the time intervals between switching on and off contactor operations. Object of research – transient thermophysical, electromechanical and electromagnetic processes in vacuum contactors for medium voltage networks. Subject of research – bistable actuators on the basis of monostable polarized electromagnets with rotary springs and microprocessor control systems for them. Research methods. Mathematical modeling of electromagnetic, mechanical and thermophysical processes in a monostable polarized electromagnet for determining the rational linear dimensions of magnetic core parts. Numerical solution of ordinary and partial differential equations is carried out in numerical software packages and codes written and verified by the applicant, which take into account the most significant interconnections between phenomena. The following scientific results are obtained in the work. In the dissertation the scientific-practical task for improving the vacuum contactors of medium voltage with monostable polarized electromagnets, in particular, for reducing the bounce of the main contacts, is one of the main requirements for these devices. The analysis of medium voltage vacuum contactors is carried out. A number of disadvantages are identified concerning both electromagnets and their control systems. The concept of contactors with bistable actuators on the basis of monostable polarized electromagnets with rotary springs using high-coercive permanent magnets is proposed and implemented. The correlation between the characteristics of a monostable polarized electromagnet and the characteristics of the rotary and contact springs, in which the requirements for vacuum interrupters relative to the speed of movement and the number of bounce of contacts are met, is established. The mathematical model of contact welding at their bounce is improved. The maximum value of the potential welding force of the contacts takes place during the operation of switching on the contactor is determined. The mathematical model of the process of switching on the contactor is improved and calculations of the dynamic characteristics of the electromagnet are carried out. On the basis of the calculations carried out, the rational parameters of the coil of the electromagnet and the capacitance of the electrolytic capacitor are chosen, in which the reliable operation of the contactor would be ensured and the requirements of the manufacturers of vacuum interrupters relative to the duration of the contact bounce and the speed of their closure are fulfilled. Experimental investigations on the number and duration of bounces of the main contacts of the vacuum contactor during the switching on operation are carried out. It is established that the new contactor fully meets the requirements of manufacturers of vacuum interrupters in relation to the duration and number of bounces, the speed of the contacts movement during the operation of switching on and switching off. The concept of constructing a microprocessor hybrid control system for monostable polarized electromagnets based on the use of an interface relay with two switching contact groups and one power transistor is proposed and implemented. The algorithm of operation of microprocessor hybrid control system for a monostable polarized electromagnet and the technique of experimental determination of time intervals between commutation moments of a transistor controlling a relay winding, and a power transistor, are developed. The minimum interval between the switching points of the interface relay and the IGBT transistor is established, which ensures coordination of their operation. A prototype of a new universal vacuum contactor with a microprocessor control system and a hybrid switching of the power supply circuit of a winding of a monostable polarized electromagnet is developed. The control of the contactor can occur in two operating modes, performing functions as a conventional monostable contactor, and a contactor with a mechanical lock, which makes it universal. The simulators of poles with vacuum interrupters, which completely reproduce the characteristics of real interrupters, simulating the influence on the mechanical characteristics of vacuum and bellows thanks to the springs installed on them, are developed to allow tests to be carried out on mechanical wear resistance without expensive vacuum interrupters. It is established that the operation of the microprocessor hybrid control system by the position sensor decreases the total time of switching on and switching off the contactor. The materials of the dissertation are used in the educational process at the Department for Electrical Apparatus of NTU "KhPI" in disciplines of specialty " 141 – Electrical Power Engineering, Electrical Engineering and Electromechanics" (specialization "141.07 Electrical Apparatus"), preparation of course works and diploma theses, as well as in research work. Dissertation work was performed at the Department of Electrical Apparatuses within the framework of the initiative research work of the National Technical University "Kharkiv Polytechnic Institute" K3301 "Improvement of vacuum switching devices" (State registration No. 0119U002552), where the applicant was the executor of separate sections. Agreement with "ABM Ampere" LLC, Kremenchuk, on scientific and technical cooperation and scientific advising on the subject "Improvement of vacuum switching devices" (No. 33/227-2019), where the applicant was the executor of separate sections.
Improvement of vacuum contactors with monostable polarized electromagnets
Keywords: дисертація; електричні апарати; комутація; методи проектування; вакуумний контактор; вакуумний переривник; мікропроцесорна система керування; інтерфейсне реле; electrical apparatus; commutation; design methods; vacuum contactor; vacuum interrupter; microprocessor control system; interface relay; 621.316.53:621.318.3